The Relationship Between Entrepreneurship Interest and Learning Outcome of Entrepreneurship SubjectFor Student at Class XII SMKN 1 Padang. - 1222-1239 , Rima Cholylah (CIVED, 2016)
The purpose of this study was to reveal the relationship between entrepreneurship interest and learning outcome of entrepreneurship subject for student at class XII SMKN 1 Padang.The design of the study is correlation, with two variables and sample collection technique was proportional random sampling which was 181 samples from 330 populations. Data was collected by questionnaire with Likert scale that consisted of four options.Data was taken by questionnaire. Data analysis technique in this research consisted of several steps which were data description, prerequisite analysis testing and hypothesis testing. From research finding, it shows that there is a relationship between entrepreneurship interest and learning outcome of entrepreneurship subject for student at class XII SMKN 1 Padang, with pearson correlation coefficient is (0.612) > alpha (0.05), this result shows a significant relationship between learning interest and learning outcome for entrepreneurship subject.Keywords: Entrepreneurship Interest, Learning Outcome.